Security and trust management : 14th International Workshop, STM 2018, Barcelona, Spain, September 6-7, 2018, Proceedings /: 14th International Workshop, STM 2018, Barcelona, Spain, September 6-7, 2018, Proceedings. (2018) - Unknown
No abstract available